Síntese, caracterização e aplicação em fotocatálise de nanocristais semicondutores de sulfeto de cádmio suportados em argila tiolada - Nascimento, Cristiane da Cunha (2011)
The challenge of nanotechnology, the science that studies the phenomena as well as the manipulation of materials at nanoscale (1-100 nm) is the control of composition, shape and size of nanoparticles, parameters that influence the physical, chemical, optical and electronic properties. In this context, the so-called quantum dots (QDs) are semiconductor nanoparticles which have attracted considerable attention due to their heavily size-dependent optical and electronic properties. Cadmium sulfide (CdS) QDs exhibit important photoluminescent properties, allowing applications in optoelectronic systems, photocatalysis, photodegradation of pollutants in the water medium etc. In this work, we present the results of the synthesis and characterization of CdS nanocrystals, in the absence and in the presence of doping Mn (II) ions, supported on Montmorillonite thiolated (MT) as well as their application as photocatalysts. The materials were characterized by UV-Vis absorption spectroscopy, X-ray diffractometry, photoluminescence spectroscopy and High-Resolution transmission electron microscopy. The effects of nanoparticle size, evaluated first by UV-visible spectroscopy, showed that the absorption maximum changed from 470 to 460 nm for different proportions of the support relative to CdS precursors. The XRD patterns showed three peaks of CdS nanocrystals related to the cubic phase of CdS. The photoluminescence spectra have shown emission bands around 470, 476, 484 and 495 viii nm, attributed to direct recombination of electron-hole pairs, and the presence of a shoulder around 578 nm, attributed to radiative recombination in trap levels from surface deffects. HRTEM images for the sample of CdS/MT 200 mg suggest the presence of monocrystalline CdS nanocrystals with approximately 4.8 nm which assemble together forming polycrystalline aggregates with a size from about 45 nm intercalated into clay layers. The photocatalytic activity of CdS/MT and CdS:Mn / MT was studied by Rhodamine 6G (R6G) photodegradation under sunlight irradiation. The results have shown a decrease in the intensity of the bands in addition to a shift from 526 to 505 nm in the absorption maximum with increasing time. According to the results of photocatalysis after 80min practically all the dye had been degraded, on the other hand, for the adsorption test, after the first 20 minutes there were no significant changes in the dye concentration. The rate of decolorization of dye showed that after 80 min the QDs have an effective induction in the degradation of R6G and the photocatalytic decolorization of R6G can be described by a pseudo first order kinetic model.